KEMITRAAN PENDIDIKAN, BUDAYA SEKOLAH, DAN PERAN GURU DALAM PENGUATAN KARAKTER SERTA JEJARING SOSIAL PENDIDIKAN (PERSPEKTIF PG-PAUD) - Rahma; Hayatun Saidah; Ulandari; Fahmi (STKIP Subang, 2026)
Early Childhood Education (ECE) is a crucial stage in establishing the foundation of character development. This article examines the integration of educational partnerships, school culture, and the role of teachers as a unified ecosystem that supports children's character development in the social networking era. Using a literature review method, the study reveals that character cannot be developed partially; rather, it requires consistent habituation across both home and school environments. The findings emphasize the importance of social media management and teacher role modeling as key factors in the successful internalization of moral values. Furthermore, the study finds that the success of character education is strongly influenced by parenting consistency, active parental involvement, and teachers’ ability to integrate character values into daily learning activities.